Comparison of Salmonella typhi and Paratyphi A Occurrence in a Tertiary Care Hospital - Kumar M., Sudeepa (JCDR Research and Publications (P) Limited, 2013)
Background: Enteric fever is an important public health problem in many underdeveloped and developing countries. In India, though Salmonella enterica serotype Typhi remains the predominant Salmonella species causing enteric fever, isolation of Salmonella enterica serotype Paratyphi A is increasing. It occurs in all age groups and more common in summer season affecting mainly children. Aims: To find out the isolation rate of Salmonella typhi and paratyphi A with reference to age, sex and seasonal variation attending a tertiary care hospital. Material and Methods: A descriptive study was done on the Salmonella species isolated from blood cultures for 5 years. Data was collected regarding basic information like age, sex, different months and years. Results: A total of 292 Salmonellae species were included in the study during the period of 5 years. Out of 292 isolates of Salmonellae, 160 were S. typhi and 132 were S. paratyphi A. Both Salmonella species showed male preponderance in all age groups. Salmonella typhi and paratyphi A were highest in the age group 11 – 20 years followed by 21 – 30 years. Highest number of cases were isolated from July – September (123 cases) followed by October – December (81 cases). Conclusion: Occurrence of S. typhi and paratyphi A are increasing which may be due to the improved diagnostics techniques or increased drug resistance. School going children and adolescents in our study were higher, requiring education classes.